Relevance of organizational commitment, as a mediator of its contribution to employee performance at the Merak-Banten marine transportation service company - Monica Pricilia Putri; Wawan Prahiawan; Agus David Ramdansyah; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become the driving force in making a real contribution to the success of the organization on an ongoing basis. Of course, only employees with optimal performance can achieve this success. However, to maximize employee performance, there must be a strategy to improve it, among others by creating employee organizational commitment. This study aims to find out how this strategy improves employee performance. This research was conducted at PT Bintang Samudra Utama Merak Banten Indonesia with a population of 76 employees while the sample used by the author, namely all the population was drawn into the sample with the Total / Saturated sampling technique. The PLS-SEM approach was used in this study. The results of this study indicate that intrinsic motivation, work discipline, and organizational commitment can be a driver in strategies to improve employee performance, either directly or indirectly optimally through organizational commitment. To be able to improve employee performance, it is necessary to improve intrinsic motivation and work discipline both directly and through organizational commitment.